2000
DOI: 10.1007/s11745-000-0564-4
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone alters lipid profiles in Zucker rats

Abstract: High free fatty acid (FFA) levels are common in obesity and in diseases such as diabetes that are associated with the obese state. Dehydroepiandrosterone (DHEA) decreases dietary fat consumption, body fat content, and insulin levels in the obese Zucker rat (ZR), a genetic model of human youth-onset obesity and type 2 diabetes mellitus. This study was conducted to investigate the effects of DHEA on lean and obese ZR serum, adipose, and hepatic tissue fatty acid (FA) profiles and serum FFA levels. Because DHEA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…This observation suggests that gaining less body weight by DHEA treatment may be responsible for lower liver steatosis [20]. Some studies reported that DHEA can decrease body weight gain [8,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that gaining less body weight by DHEA treatment may be responsible for lower liver steatosis [20]. Some studies reported that DHEA can decrease body weight gain [8,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…DHEA is considered to act as a reservoir for the subsequent production of sex steroids and a buffer hormone that changes state dependency by interacting with other hormones. There is a growing interest in DHEA with regard to clinical and pharmacological importance in fat metabolism (1,2), atherosclerosis (3,4), diabetes (5,6), hypertension (7,8) and cancer prevention (9,10). Recently, our study demonstrated that the treatment of rats with DHEA markedly increased the activity of stearoyl-coenzyme A (CoA) desaturase in the liver, leading to an increase in the content of 18:1 D in hepatic lipids (11).…”
mentioning
confidence: 83%
“…Changes in the fatty acid composition of serum, hepatic and adipose lipids in lean and obese Zucker rats, following treatment with DHEA have been reported by Abadie et al (2000). Mc Intosh et al (1999) reported decreased serum and liver lipid contents following DHEA treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Abadie et al 2000 reported that treatment with DHEA for 30 days resulted in significant alteration of fatty acid profiles of serum, hepatic and adipose lipid components in lean and obese Zucker rats. DHEA feeding also resulted in increased proportion of arachidonic acid in total lipids and decreased oleic acid in soleus as well as cardiac muscle (Abadie et al, 2001;Imai et al, 1999) reported that the increase in hepatic content of oleic acid induced by DHEA in the rat was attributable to the induction of stearoylCoA desaturase.…”
Section: Discussionmentioning
confidence: 99%